Effect of Brassica rapa L. Polysaccharide on Lewis Lung Cancer Mice by Inflammatory Regulation and Gut Microbiota Modulation - Changhui Du; Yong Zhao; Fanglin Shen; He Qian (Foods)
Lung cancer is the leading cause of cancer-related fatalities globally, related to inflammatory and gut microbiota imbalance. Brassica rapa L. polysaccharide (BP) is a functional compound, which is utilized by the gut microbiota to regulate immunity and metabolism. However, the effect of BP on lung cancer and whether it affects the “gut–lung” axis remains unclear. This study explored the intervention of BP in Lewis lung cancer (LLC) mice and its effect on the gut microbiota. The results revealed that BP reduced tumor weight and downregulated the expression of Ki67 protein. Additionally, BP reduced the content of inflammatory factors and growth factors, promoting tumor cell apoptosis and inhibiting the growth of LLC. The intervention of BP suppressed intestinal inflammation, preserved intestinal barrier integrity, and augmented the level of beneficial microbiota, such as Blautia and Bifidobacterium. Furthermore, BP significantly increased the production of short-chain fatty acids (SCFAs), particularly butyrate and propionate. A correlation analysis showed significant correlations among the gut microbiota, SCFAs, inflammatory factors, and tight junction proteins. A functional analysis indicated that BP promoted amino acid metabolism and fatty acid metabolism. These findings suggested that BP had the potential to act as prebiotics to prevent disease and improve lung cancer progression by regulating the gut microbiota.